1984
DOI: 10.7312/spea90904
|View full text |Cite
|
Sign up to set email alerts
|

Dreams of an English Eden: Ruskin and His Tradition in Social Criticism

Abstract: John Ruskin and the Ethics of Consumption-Google Books Result Dreams of an English Eden: Ruskin and his tradition in social criticism was merged with this page. Written byJeffrey L. Spear. ISBN0231055366 Dreams of an English Eden: Ruskin and His Tradition of Social. Ruskin's Culture Wars: Fors Clavigera and the Crisis of Victorian.-Google Books Result Dreams of an English Eden: Ruskin and his tradition in social criticism Dreams of an English Eden: Ruskin and his tradition in social criticism /. Social ethics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…35 The reproduction of this moral aesthetic of sympathy supports Jeffrey Spear's contention that in response 'to what he sees as the corruption of the male world of public action -economic, military, scientific -Ruskin argued for a feminisation of culture, continuing an attitude going back through his father to the late eighteenth-century "Age of Sensibility" '. 36 The ceremonial structure of the literary yearbook elevated the Ruskinian celebration of sympathy and other traditionally feminine virtues to sacred status by appropriating features of devotional literature. Joss Marsh has noted how 'over the course of the nineteenth century … literature … incrementally graduated from an oppositional to an accessory relationship to Scripture', a movement which was evident in the Victorian canonisation of Wordsworth and in George Eliot's acceptance of the Wordsworthian role of moral teacher.…”
Section: Christina Riegermentioning
confidence: 99%
“…35 The reproduction of this moral aesthetic of sympathy supports Jeffrey Spear's contention that in response 'to what he sees as the corruption of the male world of public action -economic, military, scientific -Ruskin argued for a feminisation of culture, continuing an attitude going back through his father to the late eighteenth-century "Age of Sensibility" '. 36 The ceremonial structure of the literary yearbook elevated the Ruskinian celebration of sympathy and other traditionally feminine virtues to sacred status by appropriating features of devotional literature. Joss Marsh has noted how 'over the course of the nineteenth century … literature … incrementally graduated from an oppositional to an accessory relationship to Scripture', a movement which was evident in the Victorian canonisation of Wordsworth and in George Eliot's acceptance of the Wordsworthian role of moral teacher.…”
Section: Christina Riegermentioning
confidence: 99%
“…Sharon Weltman, for instance, has demonstrated that his views often undermine strictly separate gender categories, providing an alternative image with “more power and greater responsibility” than Coventary Patmore's “Angel of the house,” which Weltman argues stems from “a very Patriarchal view of Christianity” (1998, 109). Chris Bossche (1992); Dinah Birch (2002); Deborah Nord (1988); Elizabeth Helsinger, Robin Sheets and William Veeder (1983); Paul Sawyer (1990); and Jeffrey Spear (1984), meanwhile, have all effectively contributed to elaborating on both the complexity and the progressive aspects of Ruskin's views. As a whole, however, this body of knowledge lacks a unified conceptualization that can explain the fundamental difference of Ruskin's views from the dominant views of Victorian society.…”
Section: Introductionmentioning
confidence: 99%
“…Emma Corns, Lillian Baylis, Beatrice Webb, and Elizabeth Haldane were all involved in Hill's scheme. Indeed, Hill's efforts set the scene for the Artisans Dwellings Act (1875), which was a landmark act in the creation of public housing (Spear 1984, 176).…”
mentioning
confidence: 99%
“…It has been speculated that he was descending into madness during this time, and that many of his activities, such as those at Brantwood, can be analysed in terms of the repressed 'urge to play' he experienced as a child (eg. Spear, 1984, pp. 21-22: Rosenberg.…”
mentioning
confidence: 98%